Effects of using text message interventions for the management of musculoskeletal pain: a systematic review. Issue 11 (November 2020) - Fritsch, Carolina G.; Ferreira, Paulo H.; Prior, Joanna L.; McLachlan, Andrew J.; Ferreira, Manuela L.
Abstract : Abstract: Musculoskeletal pain is the greatest cause of disability worldwide. Owing to its increasing prevalence and burden, the importance of affordable treatments has been highlighted. Text message interventions are accessible, low cost, and effective in promoting healthy behaviour and managing chronic diseases. However, little is known about their role in musculoskeletal pain. This systematic review was conducted to appraise the literature on the effects of text messages (as an intervention or a component of an intervention) compared with any control on pain and function in people with musculoskeletal pain (PROSPERO: CRD42018117371). MEDLINE, EMBASE, CINAHL, Cochrane, and PEDro databases were searched from inception to April 2020. Keywords relating to musculoskeletal pain, text messages, and randomised controlled trials were combined. Methodological quality was assessed using the PEDro score. Of the 12, 022 studies identified, 11 were included, with a mean PEDro score of 5.4/10 points (SD 1.3). Pooled analyses were not performed because of heterogeneity of interventions and clinical characteristics. When text messages were added to and compared with usual care, some positive effects were found only on treatment adherence. Although small and inconsistent, some positive effects were reported for pain intensity, function, care-seeking behaviour, adherence, and quality of life when text messages were added to multicomponent interventions. Moreover, text message and telephone counselling interventions had similar effects on function. Overall included studies were of limited methodological quality and heterogeneous. However, our results indicate potential benefits of text messages in the treatment of musculoskeletal pain, which need to be confirmed in future trials. Abstract : Supplemental Digital Content is Available in the Text.